Implementasi E-Modul dalam Peningkatan Kemandirian Belajar Peserta Didik Kompetensi Keahlian Desain Pemodelan dan Informasi Bangunan SMKN 2 Kendal - Agus, Murwo Setiyo (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The problems in this study are (1) How to plan e-modules in independent learning (2) How to implement e-module-based learning in independent learning (3) How to evaluate e-module-based learning in independent learning (4) How to increase student independence on e-module based learning. The research objectives were (1) to describe and analyze e-module planning in independent learning (2) to describe and analyze the implementation of e-module-based learning in independent learning. (3) Describe and analyze the evaluation of learning in independent learning (4) Describe and analyze the increase in student independence in e-module-based learning. This research is descriptive with a qualitative approach. Collecting data with interview techniques, observation and documentation study. Increasing the validity of research data using credibility tests and triangulation methods. Meanwhile, data analysis uses Miles and Huberman techniques, namely data collection, data condensation, data presentation and verification and drawing conclusions. The results showed that the implementation of e-modules in increasing the learning independence of students in the modeling and building information design expertise competencies of SMKN 2 Kendal had been carried out through: (1) E-module planning in independent learning includes analysis of e-module needs, design and validation (2 ) The implementation of e-module-based learning in independent learning includes giving assignments to students to study independently at home, class learning activities in the form of group discussions with guide worksheets on the e-module. Students discuss and students work on formative assessments with quizzes provided in the e-module. (3) Evaluation of e-module-based learning in independent learning includes measuring higher-level thinking skills, based on contextual problems and using various forms of questions. (4) Increasing the independence of students in e-module-based learning includes: self-confidence, active in learning, discipline in learning, responsibility in learning and motivation in learning. Conclusion: the implementation of e-modules in increasing student learning independence competency in building information and modeling design expertise at SMKN 2 Kendal through planning, implementation and evaluation of learning is in accordance with predetermined management.